The Phenomenon of Premarital Sex among Adolescents (Study in the Working Area of the Mamboro Health Center) - Nurhayati, Aprillia; Ira Nurmala; Shrimarti Rukmini Devy; Arwan (Universitas Airlangga, 2025)
Background: Over time, adolescents in Indonesia are increasingly at risk of changing their lifestyles, as evidenced by the curiosity of adolescents for information that can cause the emergence of premarital sex behavior. This behavior is perilous, it may cause imminent harm, especially to adolescent girls. Based on data from the Palu City Health Office, there were 171 cases of adolescents who had premarital sex in 2018-2021. The results of the midwife interview found that five adolescents were pregnant before marriage within the Mamboro Health Center working area in 2022. Objectives: to explore predisposing factors (knowledge and attitude), supporting factors (media influence), and driving factors (influence of health workers, family and peers) in adolescent premarital sexual behavior. Method: a qualitative study with a case study design. There were 10 informants; 1 key informant, 6 main informants, and 3 supporting informants selected by purposive sampling techniques. Results: 4 out of 6 main informants had engaged in premarital sexual behavior, while 2 others admitted they had kissed. Conclusion: Regarding the predisposing factors, knowledge related to the definition, forms, factors, and the impact of premarital sex was clearly stated by adolescents. As for attitudes, adolescents had a positive attitude or abstinance towards premarital intercourse. It was found that in the supporting factors, media influenced the adolescents in form of pornographic photos and videos. As in the driving factors, health workers, family, and peers have the influence related to information, communication, and motivation among adolescents. However, adolescents prefer to tell reproductive problems to their friends.